Improving Students’ Achievement In Descriptive Text Through the Application (STAD) Student Team Achievement Division - Sahat Tua Manalu (English Lecturers and Teachers Association (ELTA), 2022)
This study aims at improving students’ descriptive paragraph writing through STAD(Student Team Achievement Division) technique. In this study the writer conducted classroom action research. The subject of the research was 40 students of grade X SMA Negeri 1 PEGAJAHAN. Districts of Pegajahan Serdang Bedagai. There are four parallel classes that consist 40 students each class. The instruments for collecting data were writing test for quantitative data, qualitative data and questionnaire sheet,. The instrument for collecting the quantitative data was writing test while the qualitative data were gathered through the interview, diary notes and observation sheet. The qualitative data showed that the students were not interested in descriptive text. Based on the students’ scores of class x-1 taken by the English teacher for twice, it was gained that only 40% and 42% of students achieve .The minimum Completeness Criteria in writing. More than 50% of students are not able to get it.It means the ability of students is low. In this school students must achieve 70 in order to get in English subject. After having been analysed , the result of the study denotes that the students’ achievement constantly improved significantly. In conclusion, the application of Student Team Achievement Division technique can improve the students’ achievement in writing descriptive text. Keywords: Classroom Action Research Descriptive. STAD (Student Teams Achievement Division)